Middle pancreatectomy for selected pancreatic neck tumours - Lakhey, P. J.; Ghimire, B.; Khakurel, M. (Journal of Institute of Medicine Nepal, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Middle pancreatectomy has been indicated for small benign lesions located in the neck or body of the pancreas. The proponents of middle pancreatectomy argue that it preserves pancreatic exocrine and endocrine function thus avoiding pancreatic exocrine insufficiency and diabetes, and preserves spleen thereby avoiding life-threatening complication of post splenectomy sepsis. However, others express concern regarding the increased risk of pancreatic fistula and oncological adequacy. Here, we report two cases with low grade cystic neoplasm involving the neck of the pancreas that underwent middle pancreatectomy with variable outcome. DOI: 10.3126/joim.v31i3.2998 Journal of Institute of Medicine, December, 2009; 31(3) 56-58